INKAR AL-SUNNAH DI INDONESIA (Studi Analisis Tentang Pemikiran Inkar al-Sunnah Ir. M. Ircham Sutarto) - Caca Handika (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
AbstractThe history of the development of the hadith has recorded discussion of the inkar al-Sunnah.One of the causes of this movement is the occurrence of political differences among theMuslims which causes them to split into several groups or sects (firqah). The existence of thisarticle is to discuss inkar al-Sunnah in the contemporary period III in Southeast Asia, namelyIndonesia-Malaysia, but in this paper only discusses the inkar al-Sunnah in Indonesia andfocuses on Ircham Sutarto's thoughts about inkar al-Sunnah. Al-Qur'an and al-Sunnah aresources of Islamic teachings that must become guidelines for human life. But in practice thereare still people who deny al-Sunnah and only accept the Qur'an which is absolutely narratedmut mutually. This study aims to determine the character and teachings of inkar al-Sunnah inIndonesia, namely the thinking of Ircham Sutarto. This study uses a library studymethodology, which in conducting the research a researcher is confronted with variouswritten literatures which are the primary sources in this study and according to the object ofthe study. The core of this research reveals some teachings or understandings of one of theincarcerated figures of al-Sunnah in Indonesia, namely Ir. M. Ircham Sutarto, who totallyrejected al-Sunnah. One of the teachings of the inkar al-Sunnah Ircham Sutarto which iscontained in a dictate which he wrote himself by hand said that the hadith was limited to afairy tale or the story of the Prophet brought and told by people who lived 180 to 200 yearsafter the Prophet Muhammad died and the story was lets be a fake story (fictitious). In histeachings also said that before getting a revelation all humans have been lost and alsoincluded in the Prophet including Muhammad never lost, in accordance with the QS. AlBaqarah [2]: 198. According to him also that the Prophet had no right to rule over humans inreligious matters and carry it out, in accordance with the proposition of the QS. Al-Imranverse 228 translation of his version that is,